PEMANFAATAN KAYU PENGGANTI DAN SUBTITUSI PADA PEMBUATAN KAPAL KAYU DI LAMPULO BANDA ACEH - Tedi Maliyunda; Faisal Syahputra; Yusrizal (JURNAL KREASI RAKYAT, 2025)
Aceh has abundant potential resources. One of these potentials is marine and fisheries potential, this is supported by its location at the tip of the island of Sumatra. Aceh has a coastline of 2,817.9 km and a water area of ​​42,665.67 km2. This study aims to determine how much impact the scarcity of materials has on shipbuilding in Lampulo Banda Aceh, to examine the types of wood in shipbuilding and what alternatives will be used by shipbuilders in the future. This study uses a qualitative methodology with a literature study approach, observation and interviews. The results of the study show that the type of wood and the use of materials for making traditional wooden ships depend on the anatomical conditions that make them up and the chemical composition that affects the mechanical properties of the types of wood commonly used in shipbuilding in Banda Aceh. Making wooden ships in Banda Aceh, precisely in Lampulo, craftsmen use several types of wood, namely: Laban wood (Bak Mane), Giam wood (Bak Thu), Semantuk wood, and Seumawe wood. Where laban wood is used as a ship frame or ship bones and bak thu is used as a ship keel and engine bearings and ship dragons, semantuk wood as a ship bearing and seumawe wood is used as a ship body and ship floor. While other shipbuilders are also the same with the wood used only for the deck or floor used red meranti wood. Wooden shipbuilding in Lampulo, Banda Aceh City, especially to overcome the scarcity of wood in shipbuilding, several alternatives to replace and substitute wood can be considered. The use of steel for ship keels, laminated wood, and composite materials such as fiberglass, are several options explored. In addition, the use of preserved non-commercial wood types can be a solution to wooden shipbuilding in Lampulo, Banda Aceh.